2019
DOI: 10.3384/njvet.2242-458x.1992112
|View full text |Cite
|
Sign up to set email alerts
|

Motivational sources of practical nursing students at risk of dropping out from vocational education and training

Abstract: The aim of this study was to contribute to the understanding of the reasons for low or high academic motivation among practical nursing students at risk of dropping out from vocational education and training. The research data consisted of semi-structured interviews with 14 Finnish students, which were analysed by qualitative content analysis. The analysis identified six motivational sources. Two of these sources -Responsible agency and Completing out of necessity -were related to engagement in studying, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The results of this study supported the idea that youth have their own ways of thinking about career developments [7,51,52]. However, because the university's constraints on their university decisions and their overall contextual factors limited their opportunities, most were unable to exercise the career pathways that they might have decided on their own [14]. A discussion of the influences on the career decisions of the participants follows.…”
Section: Influences From the Participants' Contextual Environmentsupporting
confidence: 59%
See 3 more Smart Citations
“…The results of this study supported the idea that youth have their own ways of thinking about career developments [7,51,52]. However, because the university's constraints on their university decisions and their overall contextual factors limited their opportunities, most were unable to exercise the career pathways that they might have decided on their own [14]. A discussion of the influences on the career decisions of the participants follows.…”
Section: Influences From the Participants' Contextual Environmentsupporting
confidence: 59%
“…It was very surprising that the mismatching of major and human resources (i.e., students) was significant in the current Taiwanese university environment, particularly in the faculty of nursing. Although the current study could not represent the overall situation in Taiwan and the East Asian region, the significant results from this study may explore and contribute to an understanding of how these extreme situations [14] happen in the East Asian region [31].…”
Section: Influences From the Participants' Contextual Environmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Job nature is another consideration in individuals’ career development in the field of nursing. A recent study [ 10 ] indicated that student drop out is one of the biggest problems for nursing school leaders. Although nursing students need to pass an admission interview in order to enter a nursing training and education program, many still do not understand the nature, responsibilities, workload, and even administrative work of the job.…”
Section: Introductionmentioning
confidence: 99%